Некоторые пути изучения новогреческого языка в сопоставительном аспекте - Исаев, Э.Ш.; Георгиади, А.К. (Культура народов Причерноморья, 2004)
The great experience in studying Slavonic and German languages has been accumulated in Ukraine. The linguistic level of the Modern Greek language is still unsufficiently investigated not only abroad where Modern Greek is being studied as a foreign language, but in Greece it-self. The given article deals with the analysis of possible ways of the Modern Greek language investigating in the aspect of its comparison to German and Slavonic languages.